2006
DOI: 10.1161/circulationaha.105.544031
|View full text |Cite
|
Sign up to set email alerts
|

Role of Diuretics in the Prevention of Heart Failure

Abstract: Background-Hypertension is a major cause of heart failure (HF) and is antecedent in 91% of cases. The Antihypertensive and Lipid-Lowering Treatment to Prevent Heart Attack Trial (ALLHAT) stipulated assessment of the relative effect of chlorthalidone, lisinopril, and amlodipine in preventing HF. those individuals taking chlorthalidone versus amlodipine remained decreased but less so, whereas it was equivalent to those given lisinopril. Prior medication use, follow-up blood pressures, and concomitant medications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…It concluded that low-dose diuretics are the most effective first-line treatment for preventing the occurrence of cardiovascular disease morbidity and mortality [64]. Furthermore, reduction in arterial BP is very effective in preventing heart failure and diuretics may be superior to other antihypertensive therapies in this respect [65]. Thiazide diuretics, including thiazide-type (chlorothiazide and hydrochlorothiazide) and thiazide-like diuretics (indapamide and chlorthalidone), have been used for the treatment of hypertension for more than 5 decades and are still the most popular diuretics.…”
Section: ) Meta-analyses Of Trials With Cardiovascular Outcome Resulmentioning
confidence: 99%
“…It concluded that low-dose diuretics are the most effective first-line treatment for preventing the occurrence of cardiovascular disease morbidity and mortality [64]. Furthermore, reduction in arterial BP is very effective in preventing heart failure and diuretics may be superior to other antihypertensive therapies in this respect [65]. Thiazide diuretics, including thiazide-type (chlorothiazide and hydrochlorothiazide) and thiazide-like diuretics (indapamide and chlorthalidone), have been used for the treatment of hypertension for more than 5 decades and are still the most popular diuretics.…”
Section: ) Meta-analyses Of Trials With Cardiovascular Outcome Resulmentioning
confidence: 99%
“…These time points were chosen because they yielded the best-fitting models, according to log-likelihood scores. 26,27 Covariate adjustment in Cox models included age (introduced as an exponential term, which yielded a more robust association with mortality), gender, treatment variables and BP-monitoring variables. BMI was not included, as it did not predict mortality in this database.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in structure would affect BP reactivity, and hence its variability, during the varying stresses of the awake and asleep periods. Indeed, in the largest hypertension study to date, 26 the effect of antihypertensive medications on congestive heart failure outcome was also blunted with time. As the relationship of BP to heart failure is indisputable, similarly the blunting over time of the BPVR prediction of all-cause mortality should not be an argument to nullify its importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Clinical trial data have also revealed similar associations between diabetes and HF. In the ALLHAT, Davis et al 9 found that patients with diabetes had a nearly 2-fold risk for HF hospitalization or death after adjustment for other risk factors (RR, 1.95). The association with diabetes was independent from and equivalent in degree to that of coronary artery disease and greater than that for electrocardiographic left ventricular hypertrophy and renal dysfunction.…”
Section: Incidencementioning
confidence: 99%